The effect of organizational learning on market orientation moderated by job satisfaction - Salim Al Idrus; Ansari Saleh Ahmar; Abdussakir (Cogent Business & Management, 2018)
The study was aimed to examine the effect of organizational learning on market orientation moderated by job satisfaction. Quantitative approach was used due to the design of this study. The causal relationship of variables was understood using Structural Equation Modeling-Partial Least Squares (SEM-PLS). Population of study was 52 dairy cattle milk cooperatives in East Java. Sampling method was simple random sampling, which, after subjecting this population to this method, resulted in a sample of 46 cooperatives. Data were obtained through questionnaire where the items were prepared and processed with SmartPLS. Two results were obtained: (1) higher organizational learning was related with higher market orientation, and (2) job satisfaction had a positive effect on market orientation because it was helpful to increase market orientation of dairy cattle milk cooperatives in East Java, Indonesia.
Keywords: 650